1991
DOI: 10.1002/chin.199126080
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Hydrochlorination of Acetylene Using Gold Catalysts: A Study of Catalyst Deactivation.

Abstract: Hydrochlorination of Acetylene Using Gold Catalysts: A Study of Catalyst Deactivation.-With a view to the importance of the title reaction in the industrial process for the production of vinyl chloride monomer, the effect of a range of parameters on the deactivation rate is discussed. In combination with 197Au Moessbauer spectroscopy and X-ray diffractometry deactivation mechanisms are investigated and it is shown that deposition of carbonaceous residues is a predominant process. -(NKOSI, B.; COVILLE, N. J.; H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
196
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(205 citation statements)
references
References 1 publication
7
196
0
2
Order By: Relevance
“…The conversion increased with gold loading, selectivity was more than 99.9%. It has been reported that 1.0wt% Au loading was an appropriated compromise for Au/C catalyst [7,9,17]. However, with such an amount of gold loading, Au/C still deactivated continuously from 69 to 55% with about 14% C 2 H 2 conversion loss after 16 h. The observation was in line with previous studies [7,8].…”
Section: Catalytic Performancessupporting
confidence: 88%
“…The conversion increased with gold loading, selectivity was more than 99.9%. It has been reported that 1.0wt% Au loading was an appropriated compromise for Au/C catalyst [7,9,17]. However, with such an amount of gold loading, Au/C still deactivated continuously from 69 to 55% with about 14% C 2 H 2 conversion loss after 16 h. The observation was in line with previous studies [7,8].…”
Section: Catalytic Performancessupporting
confidence: 88%
“…These supported metal chlorides did not include gold and it was on the basis of this correlation that it was predicted that cationic gold would be the best catalyst for this reaction (22), and indeed this was subsequently confirmed (23)(24)(25). The correlation with the standard electrode potential has recently been confirmed (21) for catalysts containing 1 wt% metal (Figure 1) was short lived.…”
Section: Correlation Of Activity With the Standard Electrode Potentialmentioning
confidence: 74%
“…Earlier studies (25) have shown that the catalyst activity can be reactivated by exposure to Cl 2 , HCl and NO and in all these cases we consider the treatment leads to an enhancement in the Au 3+ content of the catalyst.…”
Section: Au Particle Size Distributions Of 1 Wt% Au/c Before and Aftementioning
confidence: 81%
“…A behavior also observed in the hydrochlorination of acetylene with several gold catalysts [25]. The reduction of Au(III) to Au(I) is highly dependent on the ligand according to Puddephat [26] which is probably due to Au(I) having a greater affinity for soft polarisable ligands than Au(III).…”
mentioning
confidence: 90%